Phorbol ester inhibits erythropoietin production in human hepatoma cells (Hep G2). - Kurtz, A; Eckardt, K; Pugh, C; Corvol, P; Fabbro, D; Ratcliffe, P (1992)
Using the human hepatoma cell line Hep G2, we have studied a possible role of protein kinase C (PKC) activity for regulation of erythropoietin (EPO) production. During a 72-h incubation, EPO production by the cells was stimulated sevenfold by exposure to low oxygen tension (1%) and threefold by exposure to cobaltous chloride (100 microM). The phorbol ester phorbol 12-myristate-13 acetate (PMA) led to a concentration-dependent inhibition of basal and stimulated EPO formation (ED50 10 nM). This decrease of EPO production, which was apparent already after 1 h of incubation with PMA, reached its maximal effect after 24 h and held on for 72 h. It was paralleled by an inhibition of the increase of EPO mRNA levels in response to stimulation. A 24-h preincubation of the cells with PMA (100 nM) virtually blunted the effect of hypoxia on EPO formation. Recovery of EPO synthesis after removal of PMA took 48-72 h. The effect of PMA on EPO production was mimicked by phorbol 12,13-dibutyrate (ED50 1 microM) but not by 4 alpha-phorbol 12,13-didecanoate. The synthetic diacylglycerol analogues oleolyl-acetylglycerol and dioctanoylglycerol (2-200 microM) also had no effect on either basal or stimulated EPO production. Treatment with PMA caused a translocation of the alpha-isoenzyme of PKC from the cytosol to the membrane after 1 h and a disappearance of the membrane-bound form after 24 h of incubation. Staurosporine and 1-(5-isoquinolinylsulfonyl)-2-methylpiperazine, two structurally different inhibitors of PKC activity, inhibited basal and stimulated EPO production with ED50 values of 9 nM and 50 microM, respectively.(ABSTRACT TRUNCATED AT 250 WORDS)